2014
DOI: 10.1519/jsc.0b013e31829d24b0
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Improves Exercise Tolerance in Recreational Soccer Players Without Concomitant Gain in Soccer-Specific Fitness

Abstract: This study investigated whether the addition of inspiratory muscle training (IMT) to an existing program of preseason soccer training would augment performance indices such as exercise tolerance and sports-specific performance beyond the use of preseason training alone. Thirty-one men were randomized across 3 groups: experimental (EXP: n = 12), placebo (PLA: n = 9), and control (CON: n = 10). The EXP and PLA completed a 6-week preseason program (2× weekly sessions) in addition to concurrent IMT with either an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 29 publications
1
57
0
1
Order By: Relevance
“…Note that subjects in Groups 1, 2, and 4 attained comparable lung volume expansion (i.e., total lung capacity -residual lung volume) (Hostettler et al, 2011). Individuals in the placebo trained Group 5, also breathed against an inspiratory resistance however the target pressure, and therefore the negative (inspiratory) pressure generated by these subjects during training, approximated only 15% PI max , also in accordance with the literature (Guy et al, 2014;Laoutaris et al, 2007;Volianitis et al, 2001).…”
Section: Respiratory Muscle Training Protocolssupporting
confidence: 84%
“…Note that subjects in Groups 1, 2, and 4 attained comparable lung volume expansion (i.e., total lung capacity -residual lung volume) (Hostettler et al, 2011). Individuals in the placebo trained Group 5, also breathed against an inspiratory resistance however the target pressure, and therefore the negative (inspiratory) pressure generated by these subjects during training, approximated only 15% PI max , also in accordance with the literature (Guy et al, 2014;Laoutaris et al, 2007;Volianitis et al, 2001).…”
Section: Respiratory Muscle Training Protocolssupporting
confidence: 84%
“…Inspiratory muscle training (IMT) applies an additional load to the diaphragm, being an accessory to the inspiratory muscles, to enhance their strength and endurance. Some research in the literature has assessed the effects of IMT in soccer players [24][25][26][27], demonstrating that the inclusion of such training in the primary soccer training process can improve inspiratory muscle strength (PI max ), expiratory muscle strength (PE max ), and exercise tolerance, and also reduce blood lactate (BLa) levels after a cycle of exercises [26]. Research conducted by Archiza et al [28] on a group of 18 female soccer players indicated that IMT could relieve the metabolism of inspiratory muscles and, as a consequence, improve muscle oxygen supply during high-intensity exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Three types of intervention were used, namely: (a) IMT in a chronic protocol (n = 7) [32,37,38,48,[58][59][60]; (b) in an acute protocol before the evaluation test (n = 2) [46,47]; (c) with a combination of chronic and acute protocols (n = 1) [50]. The chronic intervention procedure lasted between five and twelve weeks so that no homogeneity can be seen in them.…”
Section: Description Of the Interventions And The Resultsmentioning
confidence: 99%
“…In addition to biochemical and structural adaptations, training the inspiratory muscles would be useful to decrease the metaboreflex [25,26], by reducing fatigue in the respiratory muscles [27][28][29] through increased strength and endurance of the inspiratory muscles [30], in addition to lowering the lactate concentration [31][32][33][34]. All of this causes a reduction in both perceived effort [35,36] and the feeling of shortness of breath [37,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation